2011
DOI: 10.2108/zsj.28.491
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Ossification in Duck, Quail, and Zebra Finch: lntraspecific Variation, Heterochronies, and Life History Evolution

Abstract: Skeletogenic heterochronies have gained much attention in comparative developmental biology. The temporal appearance of mineralized individual bones in a species – the species ossification sequence – is an excellent marker in this kind of study. Several publications describe interspecific variation, but only very few detail intraspecific variation. In this study, we describe and analyze the temporal order of ossification of skeletal elements in the zebra finch, Taeniopygia guttata, the Japanese quail, Coturnix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 59 publications
(100 citation statements)
references
References 84 publications
5
87
0
8
Order By: Relevance
“…The first evidence of any mineralization was observed in the distal tibia of quail and duck at HH33 (data not shown), but there was no Alizarin red staining anywhere in the head skeleton of quail or duck (Figure 2A and data not shown), which is consistent with previous observations in chick and other avian species (Mitgutsch et al, 2011; Pechak et al, 1986). The bones of the craniofacial skeleton of quail and duck showed their first signs of mineralization at HH34 (Fig 2C, D).…”
Section: Resultssupporting
confidence: 90%
“…The first evidence of any mineralization was observed in the distal tibia of quail and duck at HH33 (data not shown), but there was no Alizarin red staining anywhere in the head skeleton of quail or duck (Figure 2A and data not shown), which is consistent with previous observations in chick and other avian species (Mitgutsch et al, 2011; Pechak et al, 1986). The bones of the craniofacial skeleton of quail and duck showed their first signs of mineralization at HH34 (Fig 2C, D).…”
Section: Resultssupporting
confidence: 90%
“…Three-dimensional rendering and visualization were performed using DRISHTI v. 1.0 (Drishti Paint and Render, [23]). Following the protocol of Mitgusch et al [24], observed ossified elements were tabulated for each specimen (electronic supplementary material, S1). Following Weisbecker [25], we distinguished clearly ossified bones ('B') from elements displaying barely detectable ossification ('m').…”
Section: (A) Data Collectionmentioning
confidence: 99%
“…During the last decade, advances in analytical methods now allow for explicit phylogenetic analyses of heterochrony sequences involving many types of events (cellular, molecular, genetic, and morphological) (Bininda‐Emonds et al ; Smith ). Ossification sequences of birds are little known, even when the information they provide could be useful in the determination of homologies, phylogenetic relationships, identification of taxa, or heterochronies (Feduccia and Nowicki ; Maisano ,; Maxwell ,,; Maxwell and Larsson ; Mitgutsch et al ). In addition, ossification in fossil embryos enables identification of morphological patterns in extinct groups (Organ et al ).…”
Section: Introductionmentioning
confidence: 99%